Matrix-isolation FTIR, theoretical structural analysis and reactivity of amino-saccharins: N-(1,1-dioxo-1,2-benzisothiazol-3-yl)-N-methyl amine and -N,N-dimethyl amine - Almeida, R. (2014)
In this work, two novel amino-substituted derivatives of saccharin, N-(1,1-dioxo-1,2-benzisothiazol-3-yl)-N-methyl amine (MBAD) and N-(1,1-dioxo-1,2-benzisothiazol-3-yl)-N,N-dimethyl amine (DMBAD), were synthesized and characterized, and their molecular structure and vibrational properties were investigated by matrix-isolation FTIR spectroscopy and theoretical calculations undertaken using different levels of approximation. The calculations predicted the existence of two conformers of MBAD. The lowest energy form was predicted to be considerably more stable than the second conformer (DE > ca. 20 kJ mol 1) and was the sole form contributing to the infrared spectrum of the compound isolated in solid xenon. Both conformers have planar amine moieties. In the case of DMBAD, only one doubly-degenerated-by-symmetry conformer exists, with the amine nitrogen atom considerably pyramidalized. The effect of the electron-withdrawing saccharyl ring on the C–N bond lengths is discussed. The different structural preferences around the amine nitrogen atom in the two molecules were explained in terms of repulsive interactions involving the additional methyl group of DMBAD. Observed structural features are correlated with the reactivity exhibited by the two compounds towards nucleophiles. The experimentally obtained spectra of the matrix-isolated monomers of MBAD and DMBAD were fully assigned by comparison with the corresponding calculated spectra.